Childhood Obesity in Serbia on the Rise - Lidija Marković; Višnja Đorđić; Nebojša Trajković; Predrag Božić; Szabolcs Halaši; Dragan Cvejić; Sergej M. Ostojić (MDPI AG, 2021)
The aim of the study was to examine changes in obesity prevalence among primary school children in Serbia between 2015 and 2019 rounds of the national WHO European Childhood Obesity Surveillance Initiative (COSI-Serbia). Cross-sectional studies were conducted in 2015 and 2019. The nationally representative samples of primary school children were measured for body height and weight, following the COSI protocol. Body Mass Index was calculated, and the IOTF and WHO definitions were used to classify children as overweight or obese. Participants were children of both sexes aged 7.00-8.99 years (n = 6105). Significant differences in overweight (obesity included) prevalence between two COSI rounds were identified regardless of definitions applied. According to the WHO definitions, prevalence of overweight and obesity combined increased in 7-9-year-old children in Serbia from 30.7% in 2015 to 34.8% in 2019 (z = −3.309, p < 0.05), and according to the IOTF standards, the increase from 22.8% to 30% was registered (z = −6.08, p = 0.00). The childhood overweight/obesity rate is increasing in Serbia, which places monitoring and surveillance of children's nutritional status high on the public health agenda.